Mechanical and Dynamic Analysis for Design and Development of a RoboCup SSL Dribbling Mechanism - Araújo, Victor; Silva, Edgleyson; Monteiro, João Guilherme; Sousa, Rebecca; Silva, Cecilia; Santana, Pedro Henrique; Barros, Edna (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2021)
Dribbling is a common skill among robot soccer categories such as Soccer Junior, Middle Size League (MSL), and Small Size League (SSL). The different set of rules among those categories brings particulars challenges in the dribbler design. When developing a dribbling mechanism, the designer must consider two scenarios: receiving the ball from a pass or interception and maintaining the ball possession with the robot stationary and moving. Therefore, a good dribbler design requires a damping system capable of absorbing the ball’s kinetic energy, and the dribbler must keep the ball in control as long as possible. This work presents a dynamic simulation and mechanical analysis method of the forces acting in a dribbler system, followed by tests in a real-world environment to design an efficient dribbler mechanism. Preliminary results show that the dribbler is capable to successfully absorb the impact of a ball moving with a speed of 3 m/s. Further validation tests in a competition environment show that the robot can keep the ball control moving with a linear speed from -0.5 to 1.5 m/s in the x-axis, -0.5 to 0.5 m/s in the y-axis and an angular speed from -6.5 to 6.5 rad/s.